Trypanotolerant livestock, a sustainable option for increasing livestock production in tsetse-affected areas - D'Ieteren, G.D.M. (International Laboratory for Research on Animal Diseases, 1994)
Discusses trypanotolerant livestock, commonly accepted by livestock producers that trypanotolerance is the ability of an animal to survive, reproduce and be productive without the necessity for trypanocidal drugs in an environment with trypanosomiasis, risk. Discusses constraints in conducting research on the characteristics of trypanotolerance cattle sheep and goats, such as, identification of suitable research sites with sufficient numbers of animals exposed to a sufficiently high level of natural trypanosomiasis risk. Discusses also the socioeconomic components contributing to feasibility, adoption and sustainability of the available options for controlling trypanosomiasis. Outlines priority areas for research. They are: first, to evaluate the economic and financial benefits and costs of alternative trypanosomiasis control methods (Vector control, trypanocidal drugs, use of trypanotolerant livestock); two to determine how local constraints (capital, veterinary services, herding labor, management, livestock markets) may limit the adoption of trypanosomiasis control measures; and three, to assess farmer and community incentives to contribute time and resources to disease/vector control.